Retention Protocols and Factors Affecting Retainer Choice among Iraqi Orthodontists - Mushriq F. Abid; Ali M. Al-Attar; Akram F. Alhuwaizi (Hindawi Limited, 2020)
Background. To identify the most common retention protocols practiced by Iraqi orthodontists using a specially designed e-survey. Furthermore, this study aimed to assess the effect of sociodemographic factors on the participant's choice. Methods. Two hundred and twenty-five questionnaires with 23 multiple choice questions were sent to members of the Iraqi Orthodontic Society. The questionnaire was organized into four sections representing information about sociodemographic status of the orthodontists, factors affecting the selection of the retention system, commonly used retainers in the upper arch and lower arch, and duration of the retention system. The chi-square test was used to test the significant association between different variable and sociodemographic factors. Results. The response rate was 87.5%. The majority of the respondents considered the original malocclusion (80.2%) and clinical experience (49.7%) as the main factors for choosing the retention protocol. In the maxillary arch, a combination of vacuum-formed retainer and fixed retainer (35%) was mostly applied; in the mandibular arch, a fixed retainer was mainly used (46.7%). Most of the respondents recommended initial full-time wearing of a removable appliance (78.2%), especially in the first 3-6 months (47.2%). According to the respondents, bonding a fixed retainer to all anterior teeth was most common (79.7%), fabricated, and adapted directly inside the patient's mouth (75.1%). More than half used flowable composite (54.8%) and recommend leaving the retainer forever (53.8%). Most of the variables showed a statistically significant association between the sociodemographic factors and type, duration, and fabrication of the retainer used. Conclusions. A combination of removable and fixed retainers was commonly used in orthodontics retention, and sociodemographic factors significantly affected retainer choice.